Robust blimps formation using wireless sensor based on Received Signal Strength Indication (RSSI) localization method - Herdawatie Abdul Kadir,; Mohd Rizal Arshad, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper suggests the wireless communication technique used to determine the information of blimp localization (distance and orientation) via wireless sensor network (WSN) protocol. In cooperative decentralized system, information exchanges between the agents are crucial. Each agent is required to share data to enable individual decision making task. In this work, the WSN were used as the data communications protocol which provides robust communication using the mesh networking. In order to support the multi agent communication network, the reliability of data needs to be proved. The performances of the communication selection were studied through experimental and simulation approach. The experimental results showed that the RSSI value from the device provided good statically data fit using the R-square with value of 0.947. This paper also proposed a new mobile node arrangement with hexagonal anchor node arrangement based on water particles formation. The node arrangement was simulated using the Senelex™ and showed low absolute error position thus achieving the desired cooperative system requirement.